Intellectual capital efficiency in Malaysian food and beverage industry - Ong, Tze San; Yeoh, Lay Yen; Teh, Boon Heng (Centre of Promoting Research Excellence, 2011)
This paper investigated the intellectual capital efficiency and the trends from 2008 to 2010 among Public Listed food and beverage companies under consumer product in Malaysia. VAICTM was used to compute VAIC, ICE, HCE, SCE and CEE using data from companies’ annual reports. The findings indicated that the VAIC for food category is 3.47 and 4.12 for beverage category while ICE is 3.22 for food category and 2.82 for beverage category respectively. The outcome revealed the beverage companies have greater VAIC and ICE compared to food companies over the 3 years period. The trend for VAIC and ICE of food category increased over the years whereas the trend of beverage category plummeted in 2009 from 2008 but rise again in 2010. It can be concluded that food companies are improving in the efficiency of utilizing their resources and intellectual capital to create value. The outcome of this research will be able to identify the efficiency of IC in food and beverage industry in Malaysia where the information is limited. Furthermore, this can aid the food and beverage companies to benchmark themselves to enhance value creation.